Melacak Jejak Islamisasi di Sidenreng Rappang Abad 17: Islamisasi, Sidenreng Rappang, Abad 17 - Ahmadyani SPI (Universitas Islam Negeri Alauddin, 2022)
Islamization in the kingdom of Sidenreng, took place in the 17th century AD, where the king of Sidenreng who first accepted Islam officially was Addatuang Sidenreng La Patiroi Matinroe ri Massepe in 1018 Hijriyah 1607 AD. After Islam came and was accepted in the Sidenreng kingdom during the Addatuang Sidenreng La Patiroi Matinroe ri Massepe era, Islam officially became the official religion of the kingdom. Islamization in the kingdom of Sidenreng implies that Islam is a religion of peace. Islam entered and was accepted by the people of the Sidenreng kingdom in a peaceful manner which was carried out by Datuk ri Bandang on the recommendation of Sultan Alauddin of Gowa.